2014
DOI: 10.1111/pcmr.12300
|View full text |Cite
|
Sign up to set email alerts
|

Human tyrosinase is able to oxidize both enantiomers of rhododendrol

Abstract: Racemic RS-4-(4-hydroxyphenyl)-2-butanol (rhododendrol, RD) was used as a topical skin-whitening agent until it was recently reported to induce leukoderma. We then showed that oxidation of RD with mushroom tyrosinase rapidly produces RD-quinone, which is quickly converted to RD-cyclic quinone and RD-hydroxy-p-quinone. In this study, we examined whether either or both of the enantiomers of RD can be oxidized by human tyrosinase. Using a chiral HPLC column, racemic RD was resolved optically to R(-)-RD and S(+)-R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 14 publications
5
59
0
Order By: Relevance
“…However, the oxidation products were not characterized in that study. In the present study, HPLC analysis confirmed that an initial product of the oxidation is the corresponding ortho-quinone by identifying the NaBH 4 reduction product as rhododendrol-catechol [9,10]. This primary quinone is rapidly converted to secondary products, as shown by spectrophotometry (Fig.…”
Section: Discussionsupporting
confidence: 86%
See 4 more Smart Citations
“…However, the oxidation products were not characterized in that study. In the present study, HPLC analysis confirmed that an initial product of the oxidation is the corresponding ortho-quinone by identifying the NaBH 4 reduction product as rhododendrol-catechol [9,10]. This primary quinone is rapidly converted to secondary products, as shown by spectrophotometry (Fig.…”
Section: Discussionsupporting
confidence: 86%
“…5). It is interesting that the carbonyl group in raspberry ketone structure may participate in the secondary reactions, perhaps through a tautomeric enol form, like the hydroxy group in rhododendrol [9,10]. The slow oxidation of 4-tert-butylphenol (5) was surprising when we consider its potent depigmenting effect [17].…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations